Hybrid films loaded with 5-fluorouracil and Reglan for synergistic treatment of colon cancer via asynchronous dual-drug delivery - Hairong Mao; Jianfeng Zhou; Liang Yan; Shuping Zhang; Deng-Guang Yu (Frontiers in Bioengineering and Biotechnology)
Combination therapy with oral administration of several active ingredients is a popular clinical treatment for cancer. However, the traditional method has poor convenience, less safety, and low efficiency for patients. The combination of traditional pharmaceutical techniques and advanced material conversion methods can provide new solutions to this issue. In this research, a new kind of hybrid film was created via coaxial electrospraying, followed by a casting process. The films were composed of Reglan and 5-fluorouracil (5-FU)-loaded cellulose acetate (CA) core-shell particles in a polyvinylpyrrolidone (PVP) film matrix. Microscopic observations of these films demonstrated a solid cross section loaded with core-shell particles. X-ray diffraction and Fourier-transform infrared tests verified that the Reglan and 5-FU loaded in the films showed amorphous states and fine compatibilities with the polymeric matrices, i.e., PVP and CA, respectively. In vitro dissolution tests indicated that the films were able to provide the desired asynchronous dual-drug delivery, fast release of Reglan, and sustained release of 5-FU. The controlled release mechanisms were shown to be an erosion mechanism for Reglan and a typical Fickian diffusion mechanism for 5-FU. The protocols reported herein pioneer a new approach for fabricating biomaterials loaded with multiple drugs, each with its own controlled release behavior, for synergistic cancer treatment.